Evaluation of properties and chemical recyclability of polyethylene / poly-(3-hydroxybutyrate-co-3-hydroxyvalerate) blend for sustainable packaging material - Norrahim, Mohd Nor Faiz (2014)
Polyethylene (PE) is a great packaging plastic due to its low cost, high versatility and good processability. This polymer is however non-renewable and non-biodegradable which may cause serious environmental problem. The use of renewable, biodegradable and chemically recyclable plastic such as polyhydroxyalkanoates (PHA) is more advantageous from environmental perspective despite of its high price and inferior mechanical and thermal properties. In order to get the better of both plastics, blending of these two polymers was proposed for this research. In this research, PE was blended with poly (3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV) ranging from 20 to 50 wt% of PHBV using melt blending techniques at 170oC. The PE/PHBV blend films were then evaluated in term of their mechanical, morphological, thermal and permeability properties (oxygen transmission rate, OTR and water vapor transmission rate, WVTR). It was found that the polymer blends consisted up to 30% of PHBV had a superior mechanical and permeability properties. OTR of the polymer blends containing 20 and 30% PHBV was reduced by 19 – 25% compared to that of neat PE, which indicated that PHBV functions as barrier for oxygen transmission. Meanwhile, WVTR value of PE/PHBV (70/30) increased by nearly 3-fold as compared to that of neat PE. These permeability properties may be suitable for packaging dried food products which require low OTR in order to maintain the shelf life of the products. Comparison of mechanical and permeability properties of the PE/PHBV blends with those of commercial plastics revealed that their properties are comparable. Chemical recyclability of PHA in the form of polymer blends has never been tested previously. In this study, PE/PHBV blends were subjected for isothermal pyrolysis in glass tube oven at 310oC for two purposes: i) to separate PHA from PE by exploiting their thermal stability differences, and ii) to chemically recycle PHA fraction. It was postulated that the difference in thermal stability of PHBV and PE is an advantage in this study as PHBV degraded as volatile matters at lower temperature and hence, can be separated from PE. From the results, it was revealed that PE and PHBV can be completely separated from each other after the pyrolysis. GC-MS and 1H-NMR analyses of the pyrolyzates confirmed that PHBV component in the polymer blend was successfully degraded into its volatile monomers (crotonic acid, CA and 2-pentenoic acid, 2-PA) and oligomers, suggested that chemical recycling of PHBV is possible. All in all, PE/PHBV blends of up to 30% of PHBV exhibited properties which are within acceptable range for packaging application with additional advantage in terms of oxygen and water vapor permeability. Moreover, PHBV fraction can be separated from the polymer blend after its use through pyrolysis, as PHBV can be pyrolyzed into valuable volatile matters, i.e. monomers and oligomers. The pyrolyzates recovered can be utilized for making another polymer, or can be used as chemicals. Remaining PE can be either chemically or mechanically recycled for other useful products. Overall, the characteristics of PE/PHBV blends presented herewith are in line with sustainable packaging principles and cascade utilization of polymeric materials proposed herewith may contribute positively to the economic and social.